Sowing dates and their effect on productivity and grain quality of the winter wheat varieties - L. A. Radchenko; Т. L. Ganotskaya; А. F. Radchenko; S. S. Babanina (Зерновое хозяйство России)
The analysis of the Crimean weather conditions during the autumn vegetation period of winter wheat indicates climate warming and, in this regard, the necessity to adjust the optimal sowing dates. The purpose of the current study was to estimate the productivity and grain quality of winter bread wheat varieties depending on different sowing dates. The objects of the study were five winter wheat varieties sown in 5 dates from October 1 to November 30 with an interval of 15 days. Field trials were conducted with appropriate observations, records, measurements and analyzes, according to the methodology of the State Variety Testing. Statistical processing of the trials was carried out by the B.A. Dospekhov’s method of dispersion and correlation analyzes. The study was carried out through three years, two vegetation periods of which (2017–2018 and 2019–2020) were dry, one period (2018-2019) was favorable for the development of winter grain crops. According to the results of the analysis of variance, there have been identified significant differences in the effect of all three factors (‘variety’, ‘length’ and ‘year’) and their correlation in all combinations on the productivity formation. The factors ‘sowing date’ (33%) and ‘correlation between date and year’ (49%) had the greatest influence on the productivity formation. In 2018, the most optimal for all studied varieties was the second sowing date (15.10), in 2019 it was the first (1.10), and under the conditions of 2020, the later sowing dates were more favorable, and the 4th period was marked as optimal (15.11). The mean productivity of all varieties at the optimum sowing dates was 4.0; 5.5 and 3.46 t/ha, respectively. The factors ‘sowing date’, ‘year’, and the correlation between them significantly influenced protein percentage in grain. Their effect on the manifestation of the above trait was 29%, 14% and 23%, respectively; on gluten content it was 29%, 16% and 21%, respectively.